2020
DOI: 10.1038/s41598-019-57142-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting redox metabolism: the perfect storm induced by acrylamide poisoning in the brain

Abstract: Exposure to acrylamide may lead to different neurotoxic effects in humans and in experimental animals. to gain insights into this poorly understood type of neurotoxicological damage, we used a multi-omic approach to characterize the molecular changes occurring in the zebrafish brain exposed to acrylamide at metabolite, transcript and protein levels. We detected the formation of acrylamide adducts with thiol groups from both metabolites and protein residues, leading to a quasi-complete depletion of glutathione … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…On the other hand, a number of studies support that the adult zebrafish brain exhibits an antioxidant defense system with high capacity. For instance, no lipid peroxidation was recently found in a zebrafish model for acute acrylamide neurotoxicity, despite the brain exhibited a total depletion of glutathione levels and a severely impaired thioredoxin system ( Raldúa et al, 2020 ). No lipid peroxidation was either found in the brain of zebrafish treated with paraquat at concentrations inducing 30–40% lethality, although the exposure to this herbicide resulted in a decrease in the superoxide dismutase (SOD) activity, catalase activity and GSH content ( Anand et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a number of studies support that the adult zebrafish brain exhibits an antioxidant defense system with high capacity. For instance, no lipid peroxidation was recently found in a zebrafish model for acute acrylamide neurotoxicity, despite the brain exhibited a total depletion of glutathione levels and a severely impaired thioredoxin system ( Raldúa et al, 2020 ). No lipid peroxidation was either found in the brain of zebrafish treated with paraquat at concentrations inducing 30–40% lethality, although the exposure to this herbicide resulted in a decrease in the superoxide dismutase (SOD) activity, catalase activity and GSH content ( Anand et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, a multi‐omics approach involving metabolome, transcriptome, and protein‐acrylamide adduct analyses made it possible to propose the complete AOP of acrylamide toxicity. The observed cellular events described previously are caused by an initial disruption of the main system responsible for controlling redox homeostasis and the glutathione and thioredoxin system through the formation of adducts of acrylamide with thiol groups of metabolites and proteins (Raldúa et al 2020). Another study has shown that exposure to carbon nanotubes resulted in increased levels of dopamine and serotonin neurotransmitters in the zebrafish brain (Da Rocha et al 2019), despite no specific link to phenotypic and physiological consequences.…”
Section: Assessing Molecular Changesmentioning
confidence: 99%
“…The extraction method was adapted from Raldúa D. et al (Raldúa et al, 2020). In brief, zebrafish larvae were homogenized in 500 µL of pre-chilled CHCl3:MeOH (2:1, v/v) and 20 µL of IS solution, with two 5 mm stainless beads using a TissueLyser (Qiagen, CA, USA) at 50 Hz for 4 min.…”
Section: Metabolite Extractionmentioning
confidence: 99%